Cross-Modal Recruitment of Primary Visual Cortex by Auditory Stimuli in the Nonhuman Primate Brain: A Molecular Mapping Study. (21st June 2012) - Hirst, Priscilla; Javadi Khomami, Pasha; Gharat, Amol; Zangenehpour, Shahin
Abstract : Recent studies suggest that exposure to only one component of audiovisual events can lead to cross-modal cortical activation. However, it is not certain whether such crossmodal recruitment can occur in the absence of explicit conditioning, semantic factors, or long-term associations. A recent study demonstrated that crossmodal cortical recruitment can occur even after a brief exposure to bimodal stimuli without semantic association. In addition, the authors showed that the primary visual cortex is under such crossmodal influence. In the present study, we used molecular activity mapping of the immediate early gene zif268. We found that animals, which had previously been exposed to a combination of auditory and visual stimuli, showed increased number of active neurons in the primary visual cortex when presented with sounds alone. As previously implied, this crossmodal activation appears to be the result of implicit associations of the two stimuli, likely driven by their spatiotemporal characteristics; it was observed after a relatively short period of exposure (~45 min) and lasted for a relatively long period after the initial exposure (~1 day). These results suggest that the previously reported findings may be directly rooted in the increased activity of the neurons occupying the primary visual cortex.